Two New Sexual Talaromyces Species Discovered in Estuary Soil in China - Pei-Jie Han; Jian-Qiu Sun; Long Wang (Journal of Fungi, 2021)
In the survey of mycobiota of mudflats in China, two new sexually reproducing Talaromyces sect. Talaromyces species were discovered and studied using a polyphasic approach. These species are named here Talaromyces haitouensis (ex-type AS3.160101T) and Talaromyces zhenhaiensis (ex-type AS3.16102T). Morphologically, T. haitouensis is distinguished by moderate growth, green-yellow gymnothecia, orange-brown mycelium, and echinulate ellipsoidal ascospores. T. zhenhaiensis is characterized by fast growth, absence of sporulation, cream yellow to naphthalene yellow gymnothecia and mycelium, and smooth-walled ellipsoidal ascospores with one equatorial ridge. The two novelties are further confirmed by phylogenetic analyses based on either individual sequences of BenA, CaM, Rpb2, and ITS1-5.8S-ITS2 or the concatenated BenA-CaM-Rpb2 sequences.